(How much) is the interrogative and (how much) is the accusative at (Muhdhab al-Din al-Muhalabi) The deceased in the year (572 AH) (Journal of the College of Basic Education, 2022)
He is “Muhadhdib al-Din Abu al-Mahasin Muhallab bin al-Husayn bin Barakat bin Ali bin Muhallab al-Masri, known as al-Muhalabi” () al-Bahansi () the linguist, grammarian and writer.Al-Bahansi is related to the city of “Al-Bahnasa, with the conquest, then the sukoon, and Sin, neglected, maqsura, a city in Egypt from the lower level, west of the Nile … a group of the people ofKnowledge” (), and Al-Muhalabi was nicknamed Abu Al-Mahasin (), and he was called Muhdhab Al-Din and Al-Muhallab Al-Bahansi ().